Career Women in Realizing Family Resilience: A Phenomenological and Maqasid Sharia Perspective - Nurul Hasanah; Nastangin (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
Career women are individuals who have dual roles that working outside the home and managing household responsibilities. The demands of career women in external world often lead to conflicts in household, which if not resolved promptly, can persist and even result in divorce. This practice of career women is common among the people of Cukilan Village, Suruh District, Semarang Regency. Based on the above background, the researcher focuses on investigating the reasons behind becoming a career woman and how career women achieve family resilience from a phenomenological and Maqasid Sharia perspective.This research is field research using a phenomenological approach and Maqasid Sharia. The research data sources are primary and secondary data. The data collection technique is through interviews. The results of this study show that the background of career women practices influenced by several motives, namely economic motives, social motives, educational motives, self-actualization motives, and cultural motives. From the motives underlying the practices of career women, when viewed from the perspective of Alfred Schutz's phenomenological theory are practices that are in accordance with his stated. Meanwhile, according to Jasser Auda's maqasid sharia perspective, hifz ad-din is realized by maintaining boundaries in accordance with religious rules. Hifz al-maal is realized by providing for needs of the family and children. Hifdzunnafs occurs through the realization of the functions of socialization, protection, emotional support, recreation, and love in family. Hifz al-aql is realized the function of education and providing a good religious foundation for children. Hifz an-nasl is realized by making time to gather with the family. Hifz al-'ird is realized by appearing appropriately, not excessively and not violating religious teachings. This study recommends strengthening maqāṣid-based family resilience literacy through a more equitable division of roles between husband and wife, structured communication and conflict management, and community support as well as family-friendly workplace policies.